Atmospheric precursors to the Antarctic sea ice record low in February 2022. (1st December 2022) - Yadav, Juhi; Kumar, Avinash; Mohan, Rahul
Abstract: Antarctic sea ice expansion and recession are asymmetric in nature, with regional and temporal variations. The decade-long overall increase in the Antarctic sea ice extent (SIE) until 2015 showed a decrease in recent years since satellite records were available. The present study focused on determining the atmospheric forcing and climate fluctuations responsible for the lowest SIE record in February 2022. Here, the lowest SIE record was assumed to result from the sea ice recession that began in September 2021. The SIE reached a record low of 2.16 × 10 6 km 2 in February 2022, which was 43% lower than the mean extent of the previous February months since the satellite era. However, the second-lowest SIE was recorded from November 2021 to January 2022. The Weddell Sea, Ross Sea, and Bellingshausen/Amundsen Seas (ABS) sectors experienced the maximum sea ice change on a regional scale. The record-low SIE occurred when the Amundsen Sea Low (ASL) pressure center was intensified, with the Southern Annular Mode (SAM) at its positive phase. Together, these two climate fluctuations played a role in modifying the pressure and wind patterns in Antarctica. The warm northerly winds largely contributed to decreased SIE. Further, the study investigated the Polar Cap Height (PCH), which demonstrates a strengthening of the stratospheric polar vortex and positive polarity of the SAM.